Revisiting the 2024 West Sumatra DPD Re-vote: An Analysis of Constitutional Court Decision No. 03-03/PHPU.DPD-XXII/2024 from the Perspective of Legal Ideals and Siyasah Dusturiyyah - Seprina, Silvia; Caniago, Sulastri; Rizal, Deri (UIN Mahmud Yunus Batusangkar, 2025)
This research aims to examine the implications of the Constitutional Court’s decision regarding the exclusion of Irman Gusman from the Final Candidate List (DCT) for the West Sumatra Regional Representative Council (DPD) by the General Election Commission (KPU), which was deemed to have violated his constitutional rights. The study evaluates this ruling from the perspective of the legal ideals of certainty, justice, and utility, as well as from the standpoint of Siyasah Dusturiyyah (Islamic constitutional politics). Furthermore, it assesses the impact of the decision on the implementation of a re-vote (Pemungutan Suara Ulang, PSU) in West Sumatra. Using a normative legal method and a qualitative approach, the study offers a comprehensive analysis of Constitutional Court Decision No. 03-03/PHPU.DPD-XXII/2024 concerning the electoral dispute over the DPD seat in West Sumatra. The research relies on secondary data sources, including primary legal materials such as the Court's decision, the Qur’an and Hadith, the 1945 Constitution, and relevant electoral laws, along with secondary sources such as scholarly books, academic journals, and prior research. The findings reveal that the Constitutional Court’s decision upheld legal certainty by clarifying the legal process and safeguarding constitutional rights, particularly those of Irman Gusman. In terms of justice, the decision focused mainly on substantive justice by addressing his constitutional entitlements. However, the utility of the ruling remains limited. The decision prompted a re-vote in West Sumatra to rectify irregularities in the previous election process. Nevertheless, the re-vote faced various challenges, including logistical constraints and limited public acceptance. From the perspective of Siyasah Dusturiyyah, the decision reflects a perceived lack of leadership integrity, as it deemed Irman Gusman unqualified. According to the principles of Islamic jurisprudence, when confronted with two conflicting harms (mafsadat), the lesser harm should be chosen. In this context, holding a re-vote was considered a lesser harm than ignoring a binding court ruling.